Aggressive digital papillary adenocarcinoma and sentinel node biopsy: A case report and literature review. (June 2020) - Dhillon, Priya; Powell, Barry; Mehdi, Syed
Summary: Aggressive digital papillary adenocarcinomas (ADPA) are malignant tumours of the sweat gland. Due to the high tendency to recur and metastasise, wide local resection of the lesion is recommended. However, there are a limited number of cases reporting the use of sentinel node biopsy in the management of ADPA, thus its effectiveness remains unclear. We present a case of ADPA of the right middle finger treated with digital amputation and sentinel node biopsy, and review the current literature focusing on the usefulness of sentinel node biopsy.